Age-related changes in the rhesus macaque eye. (November 2021) - Lin, Kira H.; Tran, Tu; Kim, Soohyun; Park, Sangwan; Chen, Jiajia; Stout, J. Timothy; Chen, Rui; Rogers, Jeffrey; Yiu, Glenn; Thomasy, Sara; Moshiri, Ala
Abstract: Purpose: To assess age-related changes in the rhesus macaque eye and evaluate them to corresponding human age-related eye disease. Methods: Data from eye exams and imaging tests including intraocular pressure (IOP), lens thickness, axial length, and retinal optical coherence tomography (OCT) images were evaluated from 142 individuals and statistically analyzed for age-related changes. Quantitative autofluorescence (qAF) was measured as was the presence of macular lesions as related to age. Results: Ages of the 142 rhesus macaques ranged from 0.7 to 29 years (mean = 16.4 years, stdev = 7.5 years). Anterior segment measurements such as IOP, lens thickness, and axial length were acquired. Advanced retinal imaging in the form of optical coherence tomography and qAF were obtained. Quantitative assessments were made and variations by age groups were analyzed to compare with established age-related changes in human eyes. Quantitative analysis of data revealed age-related increase in intraocular pressure (0.165 mm Hg per increase in year of age), ocular biometry (lens thickness 7.2 μm per increase in year of age; and axial length 52.8 μm per increase in year of age), and presence of macular lesions. Age-related changes in thicknesses of retinal layers on OCT were observed and quantified, showing decreased thickness of the retinal ganglion cell layer and inner nuclear layer, and increased thickness of photoreceptor outer segment and choroidal layers. Age was correlated with increased qAF by 1.021 autofluorescence units per increase in year of age. Conclusions: The rhesus macaque has age-related ocular changes similar to humans. IOP increases with age while retinal ganglion cell layer thickness decreases. Macular lesions develop in some aged animals. Our findings support the concept that rhesus macaques may be useful for the study of important age-related diseases such as glaucoma, macular diseases, and cone disorders, and for development of therapies for these diseases. Highlights: Intraocular pressure and axial length increased with age. Lens thickness did not increase with age. The presence of punctate macular lesions indicated an age-related phenomenon. qAF increased with age, but there was no decline in qAF units.